![1)\frac{17p-1}{4} *12+\frac{3-p}{6}*12<p*12\\\\3(17p-1)+2(3-p)<12p\\\\51p-3+6-2p<12p\\\\49p-12p<-3\\\\39p<-3\\\\p<-\frac{3}{39}\\\\p<-\frac{1}{13} 1)\frac{17p-1}{4} *12+\frac{3-p}{6}*12<p*12\\\\3(17p-1)+2(3-p)<12p\\\\51p-3+6-2p<12p\\\\49p-12p<-3\\\\39p<-3\\\\p<-\frac{3}{39}\\\\p<-\frac{1}{13}](https://tex.z-dn.net/?f=1%29%5Cfrac%7B17p-1%7D%7B4%7D%20%2A12%2B%5Cfrac%7B3-p%7D%7B6%7D%2A12%3Cp%2A12%5C%5C%5C%5C3%2817p-1%29%2B2%283-p%29%3C12p%5C%5C%5C%5C51p-3%2B6-2p%3C12p%5C%5C%5C%5C49p-12p%3C-3%5C%5C%5C%5C39p%3C-3%5C%5C%5C%5Cp%3C-%5Cfrac%7B3%7D%7B39%7D%5C%5C%5C%5Cp%3C-%5Cfrac%7B1%7D%7B13%7D)
1" alt="2)m*8-\frac{2m+1}{2}*8<\frac{m-5}{8}*8\\\\8m-4(2m+1)<m-5\\\\8m-8m-4<m-5\\\\-4<m-5\\\\-m<-5+4\\\\-m<-1\\\\m>1" align="absmiddle" class="latex-formula">
-\frac{3}{13}\\\\Otvet:\boxed{0}" alt="3)\frac{y-1}{5}*15-y*15<\frac{y}{15} *15\\\\3(y-1)-15y<y\\\\3y-3-15y<y\\\\-12y-y<3\\\\-13y<3\\\\y>-\frac{3}{13}\\\\Otvet:\boxed{0}" align="absmiddle" class="latex-formula">
1*15\\\\5(2y-4)-3(y+1)>15\\\\10y-20-3y-3>15\\\\7y>15+23\\\\7y>38\\\\y>5\frac{3}{7} \\\\Otvet:\boxed{6}" alt="4)\frac{2y-4}{3}*15-\frac{y+1}{5}*15>1*15\\\\5(2y-4)-3(y+1)>15\\\\10y-20-3y-3>15\\\\7y>15+23\\\\7y>38\\\\y>5\frac{3}{7} \\\\Otvet:\boxed{6}" align="absmiddle" class="latex-formula">